Five New Indole Alkaloid Derivatives from Deep-Sea Fungus Aspergillus fumigatus AF1 - Lai-Hui Dai; Gao-Rong Zhang; Yang-Hui Ou; Xiao-Jing Liu; Hong-Liang Yao; Wen-Hao Hu; Hou-Jin Li; Wen-Jian Lan (Marine Drugs)
One new gliotoxin derivative fumianthrogliotoxin (1), one new indoquizoline alkaloid N3-(methyl propionate) indoquizoline (2), and three novel indole alkaloids, anthroxyindole (3), (±)-asperfumiindole A (4), and (±)-asperfumiindole B (5), together with 16 known compounds (6–21), were isolated from the culture of deep-sea derived fungus Aspergillus fumigatus AF1. Their chemical structures and absolute configurations were determined through the analysis of NMR data in combination with electronic circular dichroism (ECD) calculations and other spectroscopic analyses. Compounds 2–11 and 13–21 were evaluated for anti-pulmonary fibrosis activity. Compounds 8 and 13 displayed significant downregulation of the mRNA expression levels of all three molecular markers (COL1A1, α-SMA and FN1), with compound 13 exhibiting the best performance among all the tested compounds.